Investment policies and telecommunications regimes - Zdenek Drabek (World Trade Organization (WTO), 2001)
The purpose of the paper is to evaluate the GATS/Telecom Agreement. This is done by looking at the guiding principles for negotiating market access for foreign investors, by comparing the Agreement with the Telecom Agreement under NAFTA and by discussing the merits of the multilateral approach to negotiating foreign investment in the telecommunication sector. The WTO GATS/Telecom Agreement comes out rather well from this evaluation exercise.
Keywords: F21; F42; L63; 330; Foreign Investment; Telecommunications